External auditor and its reliance on internal audit: The role of big data analysis - Ismail, Iyad Husni Mohammed (2024)
There is an important professional issue over the audit reliance of external auditors on internal audit, through the big data analysis role in Palestine generally, and in Gaza Strip particularly. Interestingly, the prolonged existence of the professional institutions and audit firms, which are regarded as the only ones responsible for the audit profession, obviously do not have significant exploration of the audit reliance techniques. Hence, this research mainly investigated advanced ways of enhancing the abilities of external auditors and audit firms in developing audit reliance. The exploration of such strategies necessitated the employing of a qualitative research methodology that involved multiple interviews. Consequently, the acquired primary data was then thematically analysed using NVivo 11. By adopting a grounded theory approach in data collection and analysis, an audit reliance decision theory was ultimately generated and proposed for external auditing implementation. This theory is a series of auditing procedures that improve external auditing techniques, which leads to a high-quality audit process. The research findings encompassed the extent of availability and usage of big data and big data analysis by external auditors in the Gaza Strip, Palestine. Additionally, the study investigated the role of big data analysis in external auditors' reliance on the internal audit function and explored the impact of technological, organizational, and environmental approaches on the integration of big data analysis in external auditors' reliance on the internal audit function. Therefore, this research holds significant importance for auditing firms, shedding light on their operational mechanisms to identify pivotal strategies to gain a competitive edge, offers pertinent insights into the decision-making process as a valuable resource of future information influencing numerous decisions through the released theory. Also, results would assist the auditing academics and professional institutions in developing techniques for the audit reliance decision process and enhance the external auditors’ skills.